Ahnak in the prefrontal cortex mediates behavioral correlates of stress resilience and rapid antidepressant action in mice - Bhatti, Dionnet L.; Jin, Junghee; Cheng, Jia; McCabe, Kathryn; Lee, Ko-Woon; Berdasco, Clara; Jeong, Yu Young; Sinha, Subhash C.; Kim, Yong (Frontiers in Molecular Neuroscience, 2024)
The prefrontal cortex (PFC) is a key neural node mediating behavioral responses to stress and the actions of ketamine, a fast-acting antidepressant. The molecular mechanisms underlying these processes, however, are not fully understood. Our recent study revealed a pivotal role of hippocampal Ahnak as a regulator of cellular and behavioral adaptations to chronic stress. However, despite its significant expression in the PFC, the contribution of cortical Ahnak to behavioral responses to stress and antidepressants remains unknown. Here, using a mouse model for chronic social stress, we find that Ahnak expression in the PFC is significantly increased in stress-resilient mice and positively correlated with social interaction after stress exposure. Conditional deletion of Ahnak in the PFC or forebrain glutamatergic neurons facilitates stress susceptibility, suggesting that Ahnak is required for behavioral resilience. Further supporting this notion, Ahnak expression in the PFC is increased after the administration of ketamine or its metabolite (2R, 6R)-hydroxynorketamine (HNK). Moreover, Ahnak deletion in forebrain glutamatergic neurons blocks the restorative behavioral effects of ketamine or HNK in stress-susceptible mice. This forebrain excitatory neuron-specific Ahnak deletion reduces the frequency of mini excitatory postsynaptic currents in layer II/III pyramidal neurons, suggesting that Ahnak may induce its behavioral effects via modulation of glutamatergic transmission in the PFC. Altogether, these data suggest that Ahnak in glutamatergic PFC neurons may be critical for behavioral resilience and antidepressant actions of ketamine or HNK in chronic social stress-exposed mice.